2013
DOI: 10.1128/jvi.03481-12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Protective Effect of Imvamune and Acam2000 Vaccines against Aerosolized Monkeypox Virus in Cynomolgus Macaques

Abstract: To support the licensure of a new and safer vaccine to protect people against smallpox, a monkeypox model of infection in cynomolgus macaques, which simulates smallpox in humans, was used to evaluate two vaccines, Acam2000 and Imvamune, for protection against disease. Animals vaccinated with a single immunization of Imvamune were not protected completely from severe and/or lethal infection, whereas those receiving either a prime and boost of Imvamune or a single immunization with Acam2000 were protected comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 41 publications
0
105
0
Order By: Relevance
“…A single dose of MVA-based vaccine failed to protect macaques against aerosolized monkeypox in a recent trial, though protective effects and neutralizing antibody titers similar to ACAM2000 were induced by a prime-booster sequence [120]. MVA-vaccinated monkeys challenged with monkeypox also demonstrated higher levels of viremia than Dryvax or MVA/Dryvax vaccinated monkeys, and some developed self-resolving minor monkeypox lesions while remaining otherwise healthy.…”
Section: Contemporary Vaccinesmentioning
confidence: 99%
“…A single dose of MVA-based vaccine failed to protect macaques against aerosolized monkeypox in a recent trial, though protective effects and neutralizing antibody titers similar to ACAM2000 were induced by a prime-booster sequence [120]. MVA-vaccinated monkeys challenged with monkeypox also demonstrated higher levels of viremia than Dryvax or MVA/Dryvax vaccinated monkeys, and some developed self-resolving minor monkeypox lesions while remaining otherwise healthy.…”
Section: Contemporary Vaccinesmentioning
confidence: 99%
“…This study also further characterizes the use of this challenge dose, as used previously, for testing smallpox vaccines (25). In this work, clinical signs of disease, immune cell and antibody responses, viral spread through the body, and pathological changes were examined from days 2 to 12 postchallenge.…”
mentioning
confidence: 99%
“…Various immunization studies using highly attenuated MVA in non-human primates or in clinical trials have demonstrated promising results that MVA is safe, well tolerated, and immunogenic (Earl et al, 2004;Frey et al, 2014;Greenberg et al, 2013;Hatch et al, 2013;Walsh et al, 2013;Wilck et al, 2010). Highly attenuated vaccinia, such as MVA, was shown to minimize primary cutaneous lesions induced by a challenge with replication-competent vaccinia and to reduce viral shedding, indicating that replication-incompetent vaccinia strains could serve as a primer to modulate the immune response and allow subsequent immunization with a standard vaccinia vaccine (see the review by Walsh and Dolin [2011]).…”
Section: Discussionmentioning
confidence: 99%